How Digital Advertising Exposure Translates into Purchase Intention: The Mediating Role of Advertising Content Evaluation - Prihatini Ade Mayvita; Prasetyo Yuli Usaid; Aditiyanor Aditiyanor; Imam Suharto (Universitas Pahlawan Tuanku Tambusai, 2026)
Digital platforms deliver brand advertising to consumers continuously, yet greater contact does not reliably yield stronger purchase intention, and prior work reports exposure effects that are positive in some settings and negative in others. This study asks how exposure translates into intention, treating consumers' evaluation of advertising content as the intervening mechanism rather than as a parallel predictor. Cross-sectional survey data from young Indonesian consumers of an everyday branded product were analysed using partial least squares structural equation modelling with bootstrapped indirect effects. Exposure was associated with content evaluation and with purchase intention, and content evaluation partially mediated that relationship. Advertising reach therefore supplies the opportunity for persuasion, while appraisal of content governs whether that opportunity acquires behavioural relevance